Trabalhando com violência sexual contra a criança e o adolescente: a perspectiva do psicodrama na formação dos profissionais da rede de proteção - Miyahara, Rosemary Peres (2011)
The present dissertation is inserted in the contemporary debate on professional practices towards children and adolescents in situation of sexual violence, their families and protection nets. Bringing forward from the author s experience as a teacher-supervisor of the area a critical lection of the premises which inform and construct interventions, it presents a few elements for one to think of processes of professional formation as contributions to this scenery s transformation. It emphasizes as preliminary discussion the cultural and historical processes on the construction of the basis of intrafamiliar sexual abuse and the national policy which establish the directives of confrontation. Having the Psychodrama as theoreticalmethodological referential, it proposes as empiric to the research three workgroup of Dramatical Multiplication with a group of workers of a referential service of this matter. The analysis of the workgroup contents pointed out an important discussion about the tensions between actions in this field. Among them, stands out the professionals´ distress when facing the suffering and helplessness of the users, the risks of moral guardianship lying in the victimization salvationist dichotomic model relationship; the challenges when working with the sexual aggressor as part of therapeutical investiments and the growing judiciarization of conflicts as a factor which could reduce the multiplicity of interventions. The work suggest the psychodramatic methodology as a significant provision of formation, once it has benefited not just the elucidation of imaginary and cultural lines regarding this topic, but also, and mainly, it mobilized reflections and flexibility of feelings as nuance of transformation and recognition in the work power. The text finalizes emphasizing the creative potential of workers in this area which, based in group affection, can move forward a vision and posture more positive of their professional accomplishment